Condition of Coral Diversity in Kuta Mandalika Coastal, Central Lombok Regency - Dining Aidil Candri; Bagus Hakimi; Hilman Ahyadi; I Wayan Suana; Eka Sunarwidhi Prasedya; Kartini Ambarwati; Aina Ul Mardiati (Jurnal Biologi Tropis, 2023)
Development and operational activities in KEK Mandalika can increase sedimentation of waters caused by erosion of construction material activities, this have an impact on coral reef ecosystems. Coral reef ecosystems have several important roles in support life of various aquatic organisms, Damage to the coral reef ecosystem directly and indirectly, sooner or later will threaten the sustainability of the use of these resources (social economy) and the safety of the community. Observations were conducted in KEK Mandalika coastal at 6 observation points less than 10 m. The results showed that the highest percentage of live coral cover was found in Kuta Mandalika coastal at PIT 4 area (30%, damaged category, moderate status). While the lowest percentage of coverage was at PIT 5, which was 2% (damaged category, bad status). Overall the percentage of coral cover in the Kuta Mandalika area is included in the damaged category. One of the reasons is because at the lowest tide on the beach, the volume of water is very small so that many hard corals are exposed to solar radiation. This limits the types of hard corals that can grow in the intertidal zone of Mandalika coastal. Genus diversity at this location is low, ranging from 0.0782 to 0.1288. Several genera of the Nephtheidae family dominate the observation sites and form colonies of the same genus with a fairly large distribution. The average value of environmental parameter measurements in the Mandalika coastal is included in the good category for soft coral habitat and growth.